PENGARUH FITOSTEROL TUMBUHAN LAMUN ( ENHALUS ACOROIDES) TERHADAP FERTILITAS MENCIT (MUS MUSCULUS) ICR JANTAN - St. Fatmah, Hiola; Adnan, .; Arsad, Bahri (Fakultas MIPA UNM, 2010)
In Indonesia, the high growth of population is special problem. Because of that, the government had to done something to holding the rate population problem, that one of them is Planning Family (KB) in national program. Increased of rate acceptor KB can give effect to contraception logistic crisis, so it can be decreased logistic supply. By the way, the development of contraception from plant is one of alternative that can do it. Indonesia is tropical country that have richness flora. More than 940 species that has planting and used be herbal medicine or traditional medicine and from 75th family are more than 225th plant species that used be contraception material. One of them is sea grass (Enhalus acoroides) because it?s contained steroid, that?s can be isolated from all of body plant, like roots, rhizome, and leaf. Fitosterol on leaf sea grass is very potential that it had to explore in biology aspect. It?s very important in supply steroid, to be contraception material and or medicine. This research aimed to knows the influence fitosterol of sea grass (Enhalus acoroides) to fertility of Mencit (Mus musculus) male ICR. There are four experiments (A0= control : just give it to mencit is suspension of fitosterol sea grass and A1, A2, A3 : give it to mencit is dose of fitosterol sea grass with each experiment are 25, 50 and 75 mg/kg per mencit). Rate of mencit in experiment are 60 mencit. The parameter of research are heavy of testis, epididimis and vesikula seminalis, rate and sperm mortality, and so conception from male mencit. Based on the results of that research has been done shows that the fitosterol of sea grass is making influence to mencit, like increasing of heavy of testis, epididimis and vesikula seminalis, and mortality of mencit. But it can decrease of sperm rate and conception of mencit. It?s meaning that the higher dose of fitosterol can make lower of result.